Computerized protocol of orofacial myofunctional evaluation with scores: usability and validity - Cláudia Maria de Felício; Gislaine Aparecida Folha; Alice Stahl Gaido; Márcio de Mendonça Mancine Dantas; Paulo Mazzoncini de Azevedo-Marques (CoDAS)
PURPOSE: To test the usability of Computerized Orofacial Myofunctional Evaluation (OMES) protocol and analyze its validity.METHODS: The study was divided into three stages: the first stage, production of the computerized version of OMES. The second stage was the validation of the user's interface, in which 100 OMES protocols of a database, filled in printed version, were transferred using the computerized instrument. Necessary changes to the system have occurred at this stage. In the third stage, usability of the OMES protocol in multimedia version, three evaluators transferred data from other 25 printed protocols from database for the computerized version, and the time to transfer the data of each protocol was computed and compared between examiners by one-way ANOVA. Moreover, these evaluators analyzed the usability of computerized protocol according to the "Ten principles of Heuristics usability" as described in the literature.RESULTS: The computerized protocol satisfied the principles of heuristics usability, according to the evaluation of the three Speech-Language Pathology evaluators, and the average time spent by the evaluators to transpose the data of each protocol to the software ranged from 3.1±0.75 to 3.83±0.91 minutes.CONCLUSION: The Computerized AMIOFE protocol is valid and had its usability/functionality confirmed.